Diffusivity and hydrophobic hydration of hydrocarbons in supercritical CO2 and aqueous brine - Lee, Hyeonseok; Ostadhassan, Mehdi; Sun, Zheng; Pu, Hui; Liu, Bo; Varma, Rajender S; Jang, Ho Won; Shokouhimher, Mohammadreza (RSC advances, 2020)
CO2 injection (EOR and sequestration technique) creates the amalgamation of hydrocarbons, CO2, and aqueous brine in the subsurface. In this study, molecular dynamics (MD) simulations were used to investigate the diffusivity of hydrocarbon molecules in a realistic scenario of supercritical CO2 (SC-CO2) injection in the subsurface over a wide range of pressures (50 < P < 300 bar) and aqueous brine concentrations (0, 2, and 5% brine). To overcome existing challenges in traditional diffusivity calculation approaches, we took advantage of fundamental molecular-based methods, along with further verification of results by previously published experimental data. In this regard, computational methods and MD simulations were employed to compute diffusion coefficients of hydrocarbons (benzene and pentane). It was found that the presence of water and salt affects the thermodynamic properties of molecules where the intermolecular interactions caused the hydrophobic hydration of hydrocarbons coupled with ionic hydration due to hydrogen bond and ion-dipole interactions. Based on these results, it is demonstrated that the formation of water clusters in the SC-CO2 solvent is a major contributor to the diffusion of hydrophobic molecules. The outcome at different pressure conditions showed that hydrocarbons always would diffuse less in the presence of water. The slopes of linearly fitted MSD of benzene and pentane infinitely diluted in SC-CO2 is around 13 to 20 times larger than the slope with water molecules (4 wt%). When pressure increases (100-300 bar), the diffusion coefficients (D) of benzene and pentane decreases (around 1.2 × 10-9 to 0.4 × 10-9 and 2 × 10-9 to 1 × 10-9 m2 s-1, respectively). Furthermore, brine concentration generally plays a negative role in reducing the diffusivity of hydrocarbons due to the formation of water clusters as a result of hydrophobic and ionic hydration. Under the SC-CO2 rich (injection) system in the shale reservoir, the diffusion of hydrocarbon is correlated to the efficiency of hydrocarbon flow/recovery. Ultimately, this study will guide us to better understand the phenomena that would occur in nanopores of shale that undergo EOR or are becoming a target of CO2 sequestration.